2018
DOI: 10.1007/164_2018_99
|View full text |Cite
|
Sign up to set email alerts
|

pH Modulation of Voltage-Gated Sodium Channels

Abstract: Changes in blood and tissue pH accompany physiological and pathophysiological conditions including exercise, cardiac ischemia, ischemic stroke, and cocaine ingestion. These conditions are known to trigger the symptoms of electrical diseases in patients carrying sodium channel mutations. Protons cause a diverse set of changes to sodium channel gating, which generally lead to decreases in the amplitude of the transient sodium current and increases in the fraction of non-inactivating channels that pass persistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…1 & Nav1.3 Previous studies show that an increased concentration of positively charged H + during acidosis results in the protonation of the carboxylates of the outer channel vestibule [19,25]. Although this protonation is not the only determinant of proton block, it is a key component [19,25,33,34]. To determine the extent of proton block in Nav1.1 and Nav1.3, we measured current density from the ratio of peak current amplitude to the cell membrane capacitance (pA/pF) at pH 6.4 and pH 7.4.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1 & Nav1.3 Previous studies show that an increased concentration of positively charged H + during acidosis results in the protonation of the carboxylates of the outer channel vestibule [19,25]. Although this protonation is not the only determinant of proton block, it is a key component [19,25,33,34]. To determine the extent of proton block in Nav1.1 and Nav1.3, we measured current density from the ratio of peak current amplitude to the cell membrane capacitance (pA/pF) at pH 6.4 and pH 7.4.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the interactions between the positively charged H + and pore carboxylates blocks the ion conductance pathway, which subsequently reduces sodium current [34]. As DEKA and EEDD are conserved across the sodium channel family, it is not surprising that, in all of the sodium channels studied thus far, proton block exists albeit with varying degrees [25,26]. This is particularly evident in Nav1.4 where previous studies have shown a reduction in current density that is neither statistically significant nor negligible [26,38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations